Zonasi Alterasi Hidrotermal Pada Endapan Tembaga-Emas Porfiri Berdasarkan Pemetaan Permukaan Dan Eksplorasi Geofisika Di Prospek Berambang Kecamatan Sekotong Lombok Barat Nusa Tenggara Barat - Andi Faesal; Arifudin Idrus; Djoko Wintolo (Jurusan Teknik Pertambangan, Fakultas Teknik, Universitas Bangka Belitung, 2017)
The research sites are located in the village of Berambang, Sekotong District, West Lombok Regency,West Nusa Tenggara Province. This area was dominated by volcanic rocks composed of dasiticvolcanic rock, diatrema breccia, and diorite intrusion. Berambang area shows alteration in the form ofpotassic, propylitic, advanced argillic, and argillic alterations where in some places accompanied bypyritisation and stockwork structure, the type of mineralization in this area is a porphyry copper-goldtype. In the potasic alteration zone there are minerals that have a strong anomaly response to themagnetic due to the presence of oxide minerals magnetite (Fe2O3). Mineral sulfides such as pyrite(FeS2) and chalcopyrite (CuFeS2) will also provide significant anomalous responses that have anabundance of 2-5% in the potassic zone. In a propylitic alteration zone characterized by chlorite,calcite and epidote minerals that do not respond to magnetic anomalies, the presence of pyriteminerals, hematites and chalcopyrite with abundance of ≤1% will provide some magnetic anomaly inthe propylitic zone. As for advanceargillic alteration zones characterized by mineral andalusite, aluniteand quartz, there will not be any magnetic anomalies, the phenomena was due to the rarity ofmineralization in this zone gives an insignificant anomalous impact. Meanwhile, for the argillic zonecharacterized by mineral illite, kaolinite and smectite will not have anomalous magnetic impact, veryrare mineralization in the argillic zone so that the magnetic anomaly is not significant. From the floatingEuler 3D shows an anomalous source from a depth of 0 meters to a depth of more than 400 meters.